Pengaruh Gaya Kognitif Field Dependent dan Field Independent terhadap Numerasi Matematis Siswa SMP - Dua, Gilang Kerina; Kurniasari, Ika (Universitas Negeri Surabaya, 2025)
This study aims to describe the influence of cognitive style on junior high school students' mathematical numeracy. The study used a quantitative approach with the ex post facto method. The subjects of the study were junior high school students classified based on Field Independent (FI) and Field Dependent (FD) cognitive styles. The instruments used included mathematical numeracy tests and the Group Embedded Figures Test (GEFT) to measure cognitive style. The population of this study was grade VIII students of SMP Negeri 2 Plandaan Jombang. Sampling was carried out using the purposive random sampling method so that 45 students from grade VIII C and VIII D were obtained as samples, where there were 21 FI students and 24 FD students. The results of the regression analysis showed that cognitive style had a significant effect on numeracy ability, with a coefficient of determination (R²) of 0.913. This shows that 91.3% of the variation in students' numeracy ability can be influenced by cognitive style. These findings indicate that students with Field Independent cognitive style have higher numeracy scores compared to Field Dependent students.